ASSESSMENT OF DIFFICULTIES ENCOUNTERED DURING CLINICAL PROCEDURES IN COMPLETE DENTURE FABRICATION - Devi, Sanjana; Nallaswamy, Deepak; Tulsani, Minal; Rupawat, Divya; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To assess the difficulties encountered during clinical procedures in complete denture fabrication among undergraduates.Material and methods: The present study was conducted among dental graduates across various dental colleges using a questionnaire. The questions were related to clinical procedures in the fabrication of complete dentures. A total of 26 questions based on the clinical techniques in the fabrication of complete dentures were included. The questionnaire was sent to students of various colleges using an online sharing medium. 140 responses were received from students from various colleges. The data obtained was tabulated in SPSS for windows, version 20. Descriptive statistics were analysed. Chi-square test was done to analyse association between responses to various questions. Results: It was found that the most difficult procedure was jaw relation(55.7%) followed by border moulding(31.4%). The reason for such results could be the technique sensitivity of these procedures and the limited clinical exposure to these procedures at undergraduate level.Conclusion: The data obtained from the study shows the problems faced by the practitioners during the fabrication of complete dentures. Principles and procedures that a practitioner learns in school have a widespread effect. Hence, dental educators have a heavy responsibility to inculcate the skill in their students to carry out the best possible treatment for their patients. However, there is a lack of knowledge on the problems faced from the  practitioners end. More surveys need to be conducted on dental graduates in different regions to evaluate the problems and improve the dental education in various institutes.